Arginine-Vasotocin Neuronal System in Steindachneridion parahybae (Siluriformes: Pimelodidae) and Its Influence on Artificially Induced Spawning in Captivity - Renato M. Honji; Bruno C. Araújo; Paulo H. de Mello; Martín R. Ramallo; Leonel Morandini; Danilo Caneppele; Renata G. Moreira (Fishes, 2024)
This study summarizes new data on induced spawning of Steindachneridion parahybae, focusing on the aggressive behavior of females. This study characterizes the vasotocinergic system using immunohistochemistry, highlighting the potential influence of arginine-vasotocin (AVT) on reproductive physiology. Two experimental groups were proposed: (A) control, with one female in the aquarium, and (B) experimental, with two females in the same aquarium. Dominant (D) females presented a more aggressive behavior and did not show any injury. They apparently had a length and body mass higher than injured nondominant (ND) females. The analysis identified positive AVT immunoreactive (ir) neurons exclusively within the preoptic area, including parvocellular, magnocellular, and gigantocellular subpopulations, containing fibers-ir extending into the pituitary gland. Cellular and nuclear areas were greater in D compared to ND in the magnocellular subpopulation. There were no differences between parvocellular and gigantocellular subpopulations. There was a difference on the steroid plasma profile of cortisol (more in ND than in D) and 17α,20β-dihydroxy-4-pregnen-3-one (more in D than in ND). Furthermore, control and D females presented higher optical densities for AVT-ir, gonadotropin-releasing hormone-ir, and luteinizing hormone-ir than ND. In general, there were no differences in the results of female (control group) with D females. The AVT system is highly complex, possibly counting multiple sites of action during artificial reproduction and acting directly and/or indirectly associated with behavioral and physiological changes in S. parahybae females when induced to spawning.